Enhanced thermal stability of RuO2/polyimide interface for flexible device applications. (7th September 2017) - Music, Denis; Schmidt, Paul; Chang, Keke
Abstract: We have studied the thermal stability of RuO2 /polyimide (Kapton) interface using experimental and theoretical methods. Based on calorimetric and spectroscopic analyses, this inorganic–organic system does not exhibit any enthalpic peaks as well as all bonds in RuO2 and Kapton are preserved up to 500 °C. In addition, large-scale density functional theory based molecular dynamics, carried out in the same temperature range, validates the electronic structure and points out that numerous Ru–C and a few Ru–O covalent/ionic bonds form across the RuO2 /Kapton interface. This indicates strong adhesion, but there is no evidence of Kapton degradation upon thermal excitation. Furthermore, RuO2 does not exhibit any interfacial bonds with N and H in Kapton, providing additional evidence for the thermal stability notion. It is suggested that the RuO2 /Kapton interface is stable due to aromatic architecture of Kapton. This enhanced thermal stability renders Kapton an appropriate polymeric substrate for RuO2 containing systems in various applications, especially for flexible microelectronic and energy devices.